Development of Discovery Learning Based Student Worksheet to Improve Mathematical Critical Thinking Skills: Pengembangan LKPD Berbasis Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kritis Matematis - Murni, Anastasia; Marsitin, Retno; Fayeldi, Trija (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
The purpose of this study is to achieve a level of validity and, practicality and effectiveness of learning materials made in LKPD or student worksheets based on discovery learning learning to increase the mathematically critical thinking power of learners. The study utilize addie design models composed of analysis stages, design development, implementation (application) and evaluation (completion). Research ordinances or methods used in information gathering (data) of a mathematically critical and analytical ability test. Viia class learners are subject to extensive field tests and viib class learners are subject to limited field tests. As for the accepted category in this study: (1) valid, by the acquisition of validity by 3 validator (materials, media experts and mathematicians) with an overall value value of 80,81%, (2) very practical, based on the acquisition of educational responses ata wide field test and limited field tests with an average of 91.35, (3) effective, drawn from the learner's test with an average of 77.08%. Hence, the conclusion can be drawn, is that the lto which it is developed meets a valid category, is both practical and effective for use in mathematical learning.